Enhanced tendon restoration effects of anti-inflammatory, lactoferrin-immobilized, heparin-polymeric nanoparticles in an Achilles tendinitis rat model. (1st August 2020) - Choi, Hong Joon; Choi, Somang; Kim, Jae Gyoon; Song, Mi Hyun; Shim, Kyu-Sik; Lim, Youn-Mook; Kim, Hak-Jun; Park, Kyeongsoon; Kim, Sung Eun
Highlights: LF/Hep-PLGA NPs were prepared to treat Achilles tendinitis. LF/Hep-PLGA NPs decreased the levels of pro-inflammatory cytokines in vitro . LF/Hep-PLGA NPs showed anti-inflammation effects on Achilles tendinitis. LF/Hep-PLGA NPs enhanced tendon restoration effects on Achilles tendinitis. Abstract: Gradual wear and tear can cause a local inflammatory response in tendons. The trauma and inflammatory reaction eventually impair the biomechanical properties of the tendon. In this study, we prepared lactoferrin-immobilized, heparin-anchored, poly(lactic-co-glycolic acid) nanoparticles (LF/Hep-PLGA NPs) and evaluated their in vitro anti-inflammatory effects on interleukin-1β (IL-1β)-treated tenocytes and in vivo tendon healing effects in a rat model of Achilles tendinitis. Long-term LF-deliverable NPs (LF/Hep-PLGA NPs) remarkably decreased mRNA levels of pro-inflammatory factors [cyclooxygenase-2 (COX-2), IL-1β, matrix metalloproteinase-3 (MMP-3), MMP-13, IL-6, and tumor necrosis factor-α (TNF-α)] and increased mRNA levels of anti-inflammatory cytokines (IL-4 and IL-10) in both IL-1β-treated tenocytes and the Achilles tendons of a collagenase-induced Achilles tendinitis rat model. Interestingly, anti-inflammatory LF/Hep-PLGA NPs greatly enhanced collagen content, mRNA levels of tenogenic markers [collagen type I (COL1A1), decorin (DCN), tenascin-C (TNC)], and biomechanical properties such as tendon stiffness and tensile strength. These results suggest that anti-inflammatory LF/Hep-PLGA NPs are effective at restoring tendons in Achilles tendinitis.